Sport practice with friends and perceived physical competence as predictors of physical activity in adolescents - Alvariñas-villaverde, M; Giménez de Ory, Elena; Toja-reboredo, B; González-valeiro, M (Universidad de Alicante, 2022)
Understanding which factors influence participation in physical activity is essential for the development and improvement of public health intervention. The aim of this study was to provide an explanatory prediction model for physical activity level in adolescents, involving a number of influencing variables. 576 participants took part in the study: 275 boys and 301 girls aged between 12 and 18 years old (M = 14.80; SD = 1.180). They attended one of the 11 selected schools from Galicia (Spain), chosen by sampling in the seven main urban areas in that region. The International Questionnaire on Physical Education, Health and Lifestyle was administered. The findings revealed that age, sex, physical perceived competence and sport practice with friends had statistically significant influence on physical activity index. By contrast, the influence of perception of physical attractiveness could not be confirmed. Sport practice with friends and physical perceived competence were the main predicting variables for physical activity level. All this knowledge must be taken into account by physical activity and sport professionals, such as teachers or trainers. Likewise, to improve physical perceived competence, it is essential to offer a wide variety of activities, to propose different levels of problem resolution, to help students make adaptive causal attributions based on effort, and to break gender stereotypes. Strategies involving school mates or friends in different PA and sport projects are needed. © Faculty of Education. University of Alicante
Keywords: appearance; decision trees; friendships; gender; perceived motor competence; student´s perceptions; Scopus